Total synthesis of deoxy-solomonamide B by mimicking biogenesis - Vasudevan, N.; Kashinath, K.; Reddy, D. Srinivasa (Organic Letters, 2014)
A total synthesis of Deoxy-solomonamide B was accomplished starting from tryptophan in an efficient manner by mimicking the proposed biogenetic route. The present synthesis utilizes a crotylation, oxidative cleavage of the indole moiety, and macrolactamization as key steps. The use of the indole nucleus as a masked anthranilic acid unit paves the way for the easy synthesis of related macrocycles and natural products where the ortho-acyl aniline moiety is embedded into them, which otherwise is difficult to synthesize.